Antimicrobial activities of Pseudomonas spp. strains isolated from raw milk collected in Turkey: Antimicrobial activities of Pseudomonas spp. strains. (International Journal of Scientific Research and Management (IJSRM), 2018)
In the study, a total of fifteen Pseudomonas spp. strains were analysed. All the strains were isolated from raw milk samples collected from Kayseri and Nigde provinces in Turkey. Pseudomonas spp. were characterized to species level with the use of analytical profile index. The antimicrobial activity studies were investigated by using agar-well diffusion method. From the results, it was determinated P. aeruginosa and E. coli were significantly inhibited by Pseudomonas strains. Also, It was found that Pseudomonas strains had showed inhibition effect on lactic acid bacteria and lactic acid bacteria had significantly high inhibition effect on Pseudomonas strains.